Negotiating for Democratic Communities in Schools: Principals’ Perspectives - Teresa A. Wasonga; Dana Christman (Educational Considerations, 2009)
This study explored the strategic use of negotiating as a tool for creating and enhancing democratic communities. Principals have been described as an important unit of analysis in examining leadership practice.
Keywords: research; questions; purposes; study; negotiating; participating; principals; perspectives; prosperity; communities